Nursing protagonism in vaccination and evaluation of vaccine coverage against human virus papilloma in municipalities of the 18th regional health of Paraná (Research, Society and Development, 2021)
Cervical cancer is the fourth leading cause of mortality among women. The acquisition of the disease is directly related to HPV infection. The oncogenic strains of this virus have tropism for the pelvic region and can be transmitted during sexual intercourse, becoming important in the epidemiological scenario of the young population. In view of the importance of measures aimed at preventing cervical carcinoma, the objective of the present study was to carry out a bibliographic survey of a qualitative, exploratory and documentary approach about HPV vaccination and the role of the nursing professional in this context. To this end, a search was conducted in the databases Scielo, Periódicos Capes and Biblioteca Vir¬tual de Saúde, with the descriptors Human Papillomavirus and vaccines. It was observed that vaccination rates have decreased since the HPV vaccine was instituted in the PNI in 2014. Paraná had a vaccination rate similar to the national vaccine in 2014 and 2015. In 2016 the state showed a slight increase in rates. Low adherence to vaccination is multifactorial, being directly related to the population's socioeconomic status and the amount of information that this population has access to. As a result, the nursing professional becomes an essential part of the entire epidemiological context of cervical carcinoma. It is up to this professional not only the correct application of nursing techniques in the application of the vaccine, but also the individual monitoring of each patient. Thus allowing the correction of dogmas and wrong information and bringing knowledge to the whole community.